Tourism potential of the territory in regional economic development - Kostiantyn Horb (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2016)
The concept of tourism’s potential of the territory is analyzed in this article; the concept of tourism development in the region is grounded and its overall scheme is built. The tourist potential of the territory as a base of regional tourism development is a complex system which consists of geographical «core» and «add» of other factors and conditions which promote such development. At the same time, the core of tourism’s potential in one’s turn, is considered at two levels: the first (lower) level provides a set of identified and prepared tourism resources for use and expanded tourism infrastructure which is reinforced by institutional support for tourism development. The second (top) level is a set of tourist destinations, tourist clusters, tourist landscapes and regional tourism product. In particular these innovative forms of tourism territorial units in their connection are the key indicators of regional tourism development and they should be the main object of attention of the regional administration and other entities of the regional economy which are interested in tourism development.